2020
DOI: 10.1177/0253717620929494
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Correlates of Executive Dysfunction in Schizophrenia: An Exploratory Study

Abstract: Background: Executive function (EF) impairment has been demonstrated in patients with schizophrenia. This study attempted to examine the clinical and demographic correlates associated with the different components of EF in these patients using a comprehensive battery of neuropsychological tests. Materials and Methods: Consecutive inpatients with schizophrenia in remission were recruited. The following instruments were administered: (a) Positive and Negative Syndrome Scale (PANSS), (b)World Health Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
0
0
1
Order By: Relevance
“…This is again in contrast to other studies that have reported antipsychotic dosage and history of ECT as associated with greater cognitive deficits. [ 35 , 36 ] Patients who reported a family history of schizophrenia also did not have a lower score on cognitive testing. Literature is replete with reports that cognitive dysfunction is not exclusive to patients and is often found in their first-degree relatives but to a much lesser degree.…”
Section: Discussionmentioning
confidence: 99%
“…This is again in contrast to other studies that have reported antipsychotic dosage and history of ECT as associated with greater cognitive deficits. [ 35 , 36 ] Patients who reported a family history of schizophrenia also did not have a lower score on cognitive testing. Literature is replete with reports that cognitive dysfunction is not exclusive to patients and is often found in their first-degree relatives but to a much lesser degree.…”
Section: Discussionmentioning
confidence: 99%
“…-Trình độ học vấn: Bệnh nhân có trình độ học vấn từ THPT trở lên có tỷ lệ suy giảm nhận thức ít hơn với ý nghĩa thống kê p=0,000, OR=0,311. Nghiên cứu của Noel và cs (2020) cũng cho rằng số năm học càng nhiều thì khả năng suy giảm nhận thức càng ít hơn ở nhóm bệnh nhân tâm thần phân liệt [7].…”
Section: Bàn Luậnunclassified